Pin-resolved ultra-fine-group with correction method and its application to plate-type fuel reactor analysis - Rao, Junjie; Peng, Xingjie; Yu, Yingrui; Li, Qing; Wang, Kan (Frontiers in Energy Research, 2023)
In order to perform the resonance calculation efficiently and accurately, several pin-resolved ultra-fine-group methods combining the ultra-fine-group method and Dancoff factor have been developed recently. The ultra-fine-group method is used to consider the self-shielding effect accurately in the 1-D fuel model, and the Dancoff factor is used to consider the shadowing effect in a lattice system. The pin-resolved ultra-fine-group with correction method, combining the ultra-fine-group method and Dancoff factor, is implemented in a transport code using the method of characteristic. In order to expand the application range, the pin-resolved method is extended for the plate-type fuel. Numerical results show good accuracy for the plate-type fuel reactor analysis.